Consumer Satisfaction and Expectations towards the 4G Service of Nepal Telecom: A Case of Kathmandu Valley - Bhatta, Parash (Nepalese Journal of Management, 2025)
This study examines the consumer satisfaction and expectations towards the 4G service of Nepal telecom: A case of Kathmandu Valley. Customer satisfaction is the dependent variable. The selected independent variables are speed, features, cost, reliability and availability. The primary source of data is used to assess the opinions of respondents regarding speed, features, cost, reliability, availability, and customer satisfaction. The study is based on primary data of 130 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of consumer satisfaction and expectations towards the 4G service of Nepal telecom: A case of Kathmandu Valley. The study showed a positive impact of speed on customer satisfaction. It indicates that better speed leads to increase in customer satisfactions. Similarly, the study showed a positive impact of features on customer satisfaction. It indicates that attractive features lead to increase in customer satisfactions. Likewise, the study also revealed a positive impact of cost on customer satisfaction. It indicates that affordable cost related to 4G service leads to increase in customer satisfactions. Further, the study observed a positive impact of reliability on customer satisfaction. It indicates that higher the reliability, higher would be the customer satisfactions. In addition, the study observed a positive impact of availability on customer satisfaction. It indicates that availability of 4G service as per the necessity of the customers lead to increase in customer satisfactions.